Design and Realization of Coupled Line Bandpass Filter Using Compact Structure at Frequencies of 3300 MHz – 3400 MHz for WiMAX Application - Arief Budi Santiko; Yahya Syukri Amrullah; Yuyu Wahyu; Muhammad Ilham Maulana; Bambang Setia (Jurnal Elektronika dan Telekomunikasi, 2016)
In this paper, the design of microstrip BPF (Bandpass Filter) for WiMAX (Worldwide Interoperability for Microwave Access) application has been presented. The frequency band allocations for BWA (Broadband Wireless Access) in Indonesia are 2.3; 3.3 and 5.8 GHz. This microtrip BPF is designed using parallel coupled line in compact form and it has spesific parameter, i.e. 3.35 GHz center frequency, 400 MHz bandwidth, VSWR ≤ 2, -3 dB insertion loss and matching impedance between two port is 50 Ω. The Advanced Design System (ADS) software has been used during simulation and optimization. The simulation results show that return loss S11 and insertion loss S21 are -15.31 dB and -2.2 dB at 3.35 GHz respectively. For the design verification, the prototype of the proposed design wasfabricated and measured.The results of the fabrication approach of simulation results, which have return loss value S11and insertion loss S21 of the proposed microstrip filter are -18.20 dB and -2.91 dB at 3.35 GHz respectively. The result shows that the proposed design can be implemented forWiMAX communication system applications